Pemenuhan Gizi Keluarga Penerima Bantuan Program Keluarga Harapan (Pkh) Di Kabupaten Gowa (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
The Family Hope Program (PKH) implemented by the Ministry of Social Affairs is one of the efforts to alleviate poverty in this country, targeting underprivilege ,kkkd families from poor households. The objective of this research is to identify the nutritional fulfillment of PKH recipient families and the efforts made by underprivileged families to meet their family's nutritional needs. The research utilized an observational study design with descriptive analysis using a mix of methods. The population of this study was all households receiving the Family Hope Program (PKH) in Gowa Regency. The sampling was done purposively, considering the representation of the different regions in Gowa Regency. The research findings indicate that based on food commodity indicators, the majority of PKH families consume three meals a day (80.6%). Regarding the percentage of PKH assistance utilization, 95 respondents (38.5%) utilize more than 50% of the PKH assistance, 76 respondents (30.8%) utilize 30-50%, and only 28 respondents (11.3%) utilize less than 10% of the PKH assistance in terms of food access. Based on the nutritional fulfillment status of PKH beneficiary families, the majority of respondents (72.87%) have their family's nutrition needs met. The identification results stated that the nutrition of PKH beneficiary families was adequately met based on indicators of food commodities and PKH utilization. This research has implications for improving community nutrition and supporting the Family Hope Program (PKH) which is oriented towards increasing the Community Health Index and Community Welfare Index in Gowa Regency, South Sulawesi Province.